The Managerial Challenges and Strategic Alternatives for Global Non-memory Semiconductor Companies in Korea (aSSIST Business Review, 2025)
Korea’s electronics industry has achieved remarkable growth over the past few decades, with Samsung Electronics, LG Electronics and SK Hynix, steadily increasing their global market share with their ceaseless efforts, bold investment, excellent management performance, and extensive government support to develop technologies in areas such as white goods, smartphones, electronic communication devices and memory semiconductors.However, despite the development of the electronics industry, the non-memory semiconductor market in Korea differs from the general electronics industry, and I would like to propose on strategic management based on the result of analyzing the problems through preceding study using market research, and surveys of market workers. Therefore, the overall purpose and method of research for this study are explained in Chapter 1.Chapter 2 attempted to verify in detail that the Korean market mentioned above has different characteristics from other industries through prior research. To achieve this goal, the overall ecosystem of Korean companies in the non-memory semiconductor industry and the size of the Korean semiconductor market were compared to those of global and investigated, and the distribution network structure of the Korean market in the semiconductor industry was identified.Through this process, the following management strategy problems that occurred under the structure of the non-memorysemiconductor industry were recognized. First, Korean companies’ share of the non-memory market in the Korean market compared to foreign companies is only about 3%, which means the domestic non-memory semiconductor market is monopolized by foreign semiconductor companies. Second, the Korean organizations of global non-memory semiconductor companies that have entered Korea operate only sales organizations that play a very limited role, and there are generally no organizations in Korea such as product planning, HR, research (R&D), production, and purchase. Third, due to the limited role and status of Korean organizations of global non-memory companies, employees in related industries are low in work satisfaction and immersion, and do not show high productivity. Fourth, in the non-memory semiconductor market, Korean companies are being set up at a low level or in a limited area of strategic relationship with global non-memory companies. In addition, another problem is that there is a principal-agent problem because of the distribution structure of non-memory semiconductors, and that is why the semiconductor supply chain management is not stable.Chapter 3 analyzed the results of a survey of 127 people from a total of eight companies to verify the specificity of the non-memory industry in Korea and to present new management strategy alternatives by identifying the productivity and working environment, work immersion, and work satisfaction of the industry workers. The survey targeted three companies operating branches in Korea and a global semiconductor distribution company managing its business in Korea.In Chapter 4, based on the results of these market surveys and survey analysis, the following new management strategic alternatives were suggested in this project regarding the specificity and problems of the non-memory market in Korea. First, global non-memory companies that have entered Korea are operating organizations primarily for branch-type sales in Korea, causing limitations in their roles and status. As a positive alternative to these market problems, the example of STMicro was explained and proposed. Second, the work satisfaction of industry workers is not very high due to the structure of Korea’s distribution organization. In order to fundamentally solve these problems, it is explained that related industries need to research and develop new forms of leadership that fit the cultural background of Korea. Third, it is necessary to improve the fact that Korean non-memory semiconductor companies have a very low share of the global market. To solve this problem, the government’s interest and investment, which are concentrated in memory semiconductors, should be expanded to non-memory companies.The purpose and significance of this study was to analyze market research and problems in areas that relatively lack academic research in the non-memory semiconductor industry, which plays a very important role in Korea’s electronics industry, and to suggest strategic management alternatives.
Keywords: Non-memory Semiconductor; Global Strategy; Business Strategy; Problem Solving